Growth factors induce 3T3 cells to express bFGF-binding syndecan. - Klaus Elenius; Arto Määttå; Markku Salmivirta; Markku Jalkanen (1992)
Syndecan is an integral membrane proteoglycan that putatively binds extracellular matrix molecules and growth factors at the surfaces of several cell types. Syndecan is also transiently expressed in several condensing mesenchymes after epithelial induction. In order to understand the mechanism(s) that regulate(s) syndecan expression in early mesenchymal cells, we have studied the effects of growth factors on the expression of syndecan in 3T3 fibroblasts and compared these results to NMuMG epithelial cells. Our studies indicate that (i) two developmentally important growth factors, basic fibroblast growth factor (bFGF) and transforming growth factor beta (TGF-beta), especially when administrated at the same time, increase syndecan expression in 3T3 cells both at the mRNA and protein level. (ii) Furthermore, the same growth factors also increase syndecan shedding into the culture medium of 3T3 cells. No such stimulation of syndecan synthesis or shedding was observed with NMuMG cells. (iii) Syndecan isolated from the cell surface of bFGF+TGF-beta-treated 3T3 cells binds bFGF. (iv) Induced expression of syndecan correlates with enhanced binding of bFGF to the cell surface of 3T3 cells, and (v) this interaction can be inhibited by exogenous ectodomain of syndecan. These results suggest a key role for growth factors in the regulation of syndecan expression during organogenesis and, moreover, an involvement of syndecan in the regulation of growth factor action.